Anchoring mechanism and application of hydraulic expansion bolts used in soft rock roadway floor heave control - Qingliang Chang; Huaqiang Zhou; Zhihong Xie; Shiping Shen (International Journal of Mining Science and Technology, 2013)
Comparing with the resin bolt, the hydraulic expansion bolt has different anchoring mechanism and application advantage. According to the working mechanism of the hydraulic expansion bolt, its anchoring force is expressed in four forms including support anchoring force, tension anchoring force, expansion anchoring force and tangent anchoring force, and their values can be obtained on the basis of each calculation formula. Among them, the expansion anchoring force, which is the unique anchoring force of the hydraulic expansion bolt, can provide confining pressure to increase the strength of rock. Aiming at solving the problem of stability control in the soft rock roadway in Jinbaotun Coal Mine which has a double layer of 40 U-type sheds and cannot provide enough resistance support to control floor heave, the study reveals the mechanism of floor heave in the soft rock roadway, and designs the reasonable support parameters of the hydraulic expansion bolts. The observed results of floor convergence indicate that the hydraulic expansion bolts can prevent the development and flow of the plastic zone in the floor rock to control floor heave. Research results enrich the control technology in the soft rock roadway. Keywords: Hydraulic expansion bolt, Anchoring force, Soft rock roadway, Floor heave, Shed support